PERAN KONSEP MATEMATIKA DALAM PLATFORM DIGITAL: PERSPEKTIF MAHASISWA - Daz Vholasky Anggraini; Siti Rugayah; Theysa Sahlani Pratiwi; Mutiara Praptasari (Universitas Nias Raya, 2025)
The advancement of digital technology has positioned mathematical concepts as fundamental components in the operation of various digital platforms, including search engines, social media, and e-commerce systems. This study aims to investigate the extent to which university students comprehend and recognize the integration of mathematicsparticularly logic, algorithms, and statistics within the digital tools they engage with daily. Employing a descriptive quantitative method, data were collected through an online questionnaire involving 66 students from multiple academic disciplines. The results indicate that while most participants acknowledge the presence of mathematical elements in digital systems, their understanding of the underlying processes remains limited. The primary barriers identified include insufficient mastery of foundational mathematical concepts and the lack of instructional approaches that explicitly connect mathematics to digital technologies. Nevertheless, a substantial proportion of students express strong interest in learning mathematics in more practical and technology-oriented contexts. These findings underscore the need for pedagogical strategies that contextualize mathematical theory within real-world digital environments, thereby enhancing students’ digital numeracy and analytical capabilities.